Synthesis, Characterization, Antimicrobial of Studies New 2, 2'-[(1Z, 2Z)-ethane-1, 2 Diylidenedi (2Z) Hydrazin-1-yl-2-ylidene] bis (5-phenyl-1, 3, 4-Oxadiazole) and their Transition Metal Complexes - Ibrahim A. Flifel (Journal of Global Pharma Technology, 2018)
A new ligand 2,2'-[(1Z,2Z)-ethane-1,2-diylidenedi(2Z)hydrazin-1-yl-2-ylidene]bis(5-phenyl-1,3,4-oxadiazole) and its Cr (III) , Co (lll) and Ni (ll) complexes were synthesized . The new ligand and its complexes have been characterization on the basis their spectra of1HNMR, mass, Fourier transform infrared (FTIR), as well as magnetic susceptibility, elemental analysis[C, H, N] and conductance measurements. The program of hyper hem 7.51 has been used up for theoretical accounts using PM3 method [1] to study the electrostatic potential that provided good information about the complexity site. Of the results obtained we can suggest octahedral geometrics for Cr (III) and Co (III) complexes, while tetrahedral geometry for Ni (II) complex. A ligand and its complexes were screened for their antibacterial activity against two kinds of strains Escherichia coli (gram negative bacterial strains) and staphylococcus aureus (gram positive bacteria strains), this research showed excellent results in comparison with Ciprofloxacin as standard drug.Keywords: Ligand, Complexes, Characterization, Hyper Chem, Electrostatic potential, Antibacterial.